17q12 Microduplications: A challenge for clinicians. (March 2015) - Bertini, V.; Orsini, A.; Bonuccelli, A.; Cambi, F.; Del Pistoia, M.; Vannozzi, I.; Toschi, B.; Saggese, G.; Simi, P.; Valetto, A.
<x xml:space="preserve">Abstract</x> In the recent years, some cases of 17q12 deletions and duplications have been reported, but the clinical impact of these imbalances is still to be fully elucidated. In particular, 17q12 duplications elude syndrome classification, since they are associated with a wide phenotypic spectrum, ranging from very mild to quite severe phenotypes. Here, two unrelated patients with the same 1.2 Mb microduplication of 17q12 are reported. Comparing these patients' phenotype with those previously published, it emerges that the more patients reported, the more difficult is finding common characteristics, even in presence of exactly the same genetic anomaly. The role of the genes duplicated in this region and the impact of this chromosomal imbalance are discussed.© 2015 Wiley Periodicals, Inc.